Classroom Discourse Analysis in Code Switching Used by the Lecturers at IAIN Parepare - Sabolla, Munawir (STAIN Majene, 2023)
Most of the lecturers in IAIN Parepare uses two or more languages in explaining some topics. This research was conducted to find out the types of code switching that the lecturers produce in the teaching process, and to find out the reasons of the lecturers in using code switching in teaching. The researchers applied descriptive qualitative research. The subject of this research was the lecturers of English Department at IAIN Parepare consisted of 2 male and 2 female lecturers. The data of this research were collected by observation checklist and interview. The obtained data were analyzed in three major phases namely data reduction, data display, and data verification. The result of this research shows that the types of Code-Switching used by the lecturers (both male and female lecturers) of English department are Situational Code-switching and Metaphorical Code-switching. About the factors or reasons, they use Code-switching because of many reasons namely: lack of knowledge, attending of a person that do not know the language, Stylistic device, and to impress another people. Besides the four factors, English lecturers also use Code-switching based on the other three factors that freshly identified by the researchers they are: to regain the students’ attention/focus, to clear up the explanation, and to create a different learning atmosphere.